2015
DOI: 10.1007/s00401-015-1524-y
|View full text |Cite
|
Sign up to set email alerts
|

Microglia–blood vessel interactions: a double-edged sword in brain pathologies

Abstract: Microglia are long-living resident immune cells of the brain, which secure a stable chemical and physical microenvironment necessary for the proper functioning of the central nervous system (CNS). These highly dynamic cells continuously scan their environment for pathogens and possess the ability to react to damage-induced signals in order to protect the brain. Microglia, together with endothelial cells (ECs), pericytes and astrocytes, form the functional blood-brain barrier (BBB), a specialized endothelial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(155 citation statements)
references
References 186 publications
2
153
0
Order By: Relevance
“…Acquired and non-acquired disease states such as stroke, Alzheimer’s disease and others are associated with abnormal vascular function 19,20 . While extensive literature exists on stroke and its vascular effects/defects, there are scant reports related to traumatic brain injury (TBI).…”
Section: Discussionmentioning
confidence: 99%
“…Acquired and non-acquired disease states such as stroke, Alzheimer’s disease and others are associated with abnormal vascular function 19,20 . While extensive literature exists on stroke and its vascular effects/defects, there are scant reports related to traumatic brain injury (TBI).…”
Section: Discussionmentioning
confidence: 99%
“…The central nervous system (CNS) has been considered an immunologically privileged site since it is distinctly separated from the peripheral immune system by the blood-brain barrier (BBB) [36]. However, it has emerged that immune B and T cells can infiltrate into the CNS from the periphery and mediate protracted but specific immune responses.…”
Section: Inflammationmentioning
confidence: 99%
“…We therefore continued our studies to further understand the progression of this chronic, debilitating disease, by correlating cytokine, protein and neurotrophic factor concentrations and localizations, together with immune cell numbers and a loss of vascular integrity. This focus was partly due to recent research into vascular integrity and blood vessel function during chronic inflammation [23][24][25]. Using fluorescent tags and deconvolution imaging we examined vascular content, vessel integrity and vessel types in images of LPS treated rat olfactory bulbs and concluded that, by and large, vessels are overall intact but with 'suspect' areas.…”
Section: Introductionmentioning
confidence: 99%